Effect of Red Betel Leaf Extract (Piper Crocatum) on Blood Glucose Levels and Kidney Histopathology in Streptozotosin-Nicotinamide Induced Streptozotosin-Nicotinamide Rats - Navirius, Franz June; Pamudji , Gunawan; Herowati, Rina (Journal La Medihealtico, 2023)
Diabetic nephropathy is a complication of diabetes mellitus which results in changes in the structure and function of the kidneys. Red betel leaf (Piper crocatum) can be used as a treatment for diabetic nephropathy, which has antioxidant properties. This study aims to determine the optimal dose of ethanol extract of red betel leaves, the effect of ethanol extract of red betel leaves on blood glucose, improvement of kidney function and kidney histopathology in STZ-NA induced rats. This study used 30 male white rats of the Wistar strain, 5 groups were conditioned to experience hyperglycemia and waited for three weeks after induction of STZ-NA via intra peritoneal 60 mg/kg BW and 120 mg/kg BW. After it was stated that the rats had diabetic nephropathy, they were given an oral test preparation. Parameters measured were blood glucose, BUN, and renal histopathological tests. Data analysis used the ANOVA method followed by the LSD Post Hoc test. The test results of antihyperglycemic activity and improvement of kidney function stated that the ethanol extract of red betel leaves at doses of 125 mg/kg BW and 250 mg/kg BW had a significant difference between the normal group, negative control and positive control, but at a dose of 500 mg/kg BW there was no difference significantly with the positive control where the ethanol extract of red betel leaves has the same effect as the positive control. The results of the renal histopathological test at a dose of 250 mg/kg BW were significantly different from the normal control, negative control, positive control, but at a dose of 500 mg/kg BW there was no difference from the positive group.